Collagen-targeted Molecular Imaging in Diffuse Liver Diseases - Zhou, Iris Y. (Abdom Radiol (NY), 2020)
Liver fibrosis is a common pathway shared by all progressive chronic liver disease (CLD) regardless of the underlying etiologies. With liver biopsy being the gold standard in assessing fibrosis degree, there is a large unmet clinical need to develop noninvasive imaging tools that can directly and repeatedly quantify fibrosis throughout the liver for a more accurate assessment of disease burden, progression, and treatment response. Type I collagen is a particularly attractive target for molecular imaging as its excessive deposition is specific to fibrosis, and it is present in concentrations suitable for many imaging modalities. Novel molecular MRI contrast agents designed to bind with collagen provide direct quantification of collagen deposition, which have been validated across animal species and liver injury models. Collagen targeted molecular imaging probes hold great promise not only as a tool for initial staging and surveillance of fibrosis progression, but also as a marker of fibrosis regression in drug trials.